HPB P23 Laparoscopic lumen-guided cholecystectomy in face of the difficult gallbladder. (7th December 2022) - Lucocq, James; Taylor, Aaron; Driscoll, Peter; Naqvi, Syed; MacMillan, Alasdair; Bennett, Stephen; Luhmann, Andreas; Robertson, Andrew
Abstract: Background: Where the critical view of safety cannot be established during cholecystectomy, certain salvage techniques are indicated to reduce the likelihood of bile duct injury. The present study describes a salvage technique termed the "laparoscopic lumen-guided cholecystectomy" (LLC) and reports its peri-operative outcomes. Methods: A summary of the technique is as follows: (1) Hartmann's pouch is incised and stones are evacuated; (2) the cystic anatomy is inspected from the inside of the gallbladder; (3) the lumen is used to guide retrograde dissection towards the cystic pedicle; (4) cystic duct control is achieved if deemed safe. LLC cases performed between June 2020 and January 2022 in a single health board were included. The operative details and peri-operative outcomes of the technique are reported and compared to cases of similar difficulty (Nassar ≥4) where the LLC was not attempted. Results: LLC was performed in 4.6% (27/587) of cases. In all 27 cases, LLC was performed for a "frozen" cholecystohepatic triangle. Hartmann's pouch was completely excised in all cases (27/27) and cystic duct control was achieved in 85.2% of cases (23/27). No cases of bile leak or ductal injury were reported. Rates of bile leak, post-operative complications and ERCP were lower following LLC compared to the group where LLC was not attempted (p<0.01). Conclusions: LLC is a safe salvage technique and should be considered in cases where the critical view of safety cannot be established. The technique achieves cystic duct control in the majority of cases and favourable outcomes in the face of a difficult cholecystectomy.